Permasalahan Pembinaan Warga Gereja Di Kewari - Ruat Diana (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2018)
Ruat Diana, This article discusses the issue of church community development in Kewari. The main focus of this article is the difficulty of fostering church members to the Kewari community. Through this research, the authors describe the factors behind the difficulty of fostering church members in Kewari. These factors are seen from social and historical aspects. The author assesses the importance of exposing it as a reflection in carrying out church community development. The pattern of community life, language differences and the slow adjustment of language, the level of community education, and the beliefs of the community became a factor of difficulty of building church people in Kewari Ruat Diana, Permasalahan Pembinaan Warga Gereja di Kewari. Artikel ini membahas ten-tang permasalahan pembinaan warga gereja di Kewari. Fokus utama dari artikel ini adalah faktor kesulit-an pembinaan warga gereja kepada masyarakat Kewari. Melalui penelitian ini, penulis menggambarkan faktor-faktor yang melatarbelakangi kesulitan pembinaan warga gereja di Kewari. Faktor-faktor tersebut dilihat dari aspek sosial dan sejarah. Penulis menilai pentingnya memaparkan hal tersebut sebagai sebuah refleksi dalam melaksanakan pembinaan warga gereja. Pola hidup masyarakat, perbedaan bahasa dan lambatnya penyesuaian bahasa, tingkat pendidikan masyarakat, dan keyakinan masyarakat menjadi faktor kesulitan pembinaan warga gereja di Kewari.